INTERDEPENDENSI AKTOR DALAM PROSES PRODUKSI KOMODITAS CABAI DI KECAMATAN KUMPEH KABUPATEN MUARO JAMBI - Kayla Putri Zahra; Retna Hanani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
This study aims to analyze the forms of actor interdependency in the production process of chili commodities in Kumpeh District, Muaro Jambi Regency, and to identify the driving and inhibiting factors within these dependency relationships. The challenges in chili production in this area are not solely related to technical cultivation aspects, but also reflect a gap between local government policies and farmers’ needs in the field. The involvement of Bank Indonesia as a non-governmental actor in the development of the chili cluster has contributed to a shift in farmers’ dependency patterns, indicating the dynamics of network governance within the regional agricultural sector. This research employs a descriptive qualitative method using in-depth interviews with key informants. The analysis focuses on identifying patterns of resource exchange, forms of dependency relationships, and the quality of coordination among actors. The findings reveal that interdependency among actors has emerged based on mutual awareness of their respective resource limitations and capacities. However, these relationships remain largely pragmatic and have not yet been institutionalized within a shared regulatory framework, resulting in asymmetric dependency patterns that do not fully reflect optimal network coordination. The driving factors of interdependency include actors’ awareness of the need for collaboration, the responsiveness and flexibility of Bank Indonesia’s programs, and the leadership initiatives of village governments. Meanwhile, the main inhibiting factors consist of ineffective bureaucratic communication, unclear cross sectoral coordination mechanisms, limited capacity of agricultural extension officers, and ecological factors in the form of recurring annual floods that have not been integrated into program planning. This study concludes that the existing interdependency remains pragmatic and asymmetric in nature. It recommends the institutionalization of coordination mechanisms through joint standard operating procedures and the synchronization of the government’s budgeting calendar with the actual planting cycles of farmers in the field.